Analysis Of The Role Of Internal Communication And Work Discipline On Employee Performance At Pt. Kalibaru Investama - Rosary, Juao C. Costa; Ghauri, Pervez N; Salzberger, Thomas (Yayasan Pendidikan Belajar Berdikari, 2022)
This study explains the relationship between internal communication and work discipline and how both factors affect employee performance. PT. Kalibaru Investama is the subject of this investigation. The philosophy of work discipline and internal communication is covered in this paper. This study employed a non-probability sampling technique with a quantitative approach using a questionnaire survey that was given to 67 respondents and then analyzed using SPSS version 20.0. The findings of the hypothesis test (t test), which found a significant relationship between work discipline and performance (t count 2.153 Ttable 1.996). Internal communication has a t count of 3.398 Ttable 1.996 with a coefficient of determination of 41.7%, which indicates a considerable impact on job performance. Employee performance is significantly and simultaneously impacted by work discipline and internal communication. The results of this study's implications can help management, particularly at PT. Kalibaru Investama, realize the need of maintaining workplace discipline and effective internal communication.